Estudio de los macroelementos secundarios (Calcio, Magnesio y Azufre) en la calidad nutricional del pasto Saboya (Megathyrsus maximus)” - Lúa Goyes, Kimberly Yuleen (2020)
Pastures are considered as grass or legume plants that are cultivated for the purpose of feeding livestock. Many of these have a high content of proteins, carbohydrates and minerals, which allow them to gain weight, meat and in many cases obtain quality derivatives such as milk, cheese, etc. The grasses have resistance to constant trampling and good regrowth capacity In Ecuador, the agricultural work area in 2016 was 5.39 million hectares, the largest area of this soil is used for the cultivation of pastures with 42.6%.. correspond to cultivated and natural pastures. It is considered a perennial tropical grass, being of great importance in the agricultural sector due to its tolerance to droughts, it maintains a high nutritional quantity, excellent palatability and digestibility. Savoy grass can be cultivated in South America, because it has the ability to adapt to types of soils with high and medium fertility levels. Therefore, we can say that the abundant forage production is one of the peculiarities of Savoy grass, provided that it presents the optimal and favorable conditions. During the conservation process the grass maintains its nutritional value allowing the animal to take advantage of it very well. To obtain a good quality grass, it is essential to develop the different cultural tasks, one of the main ones being fertilization that will favor development, growth, nutritional content and adaptability. Fertilization in Savoy grass is based on a nutritional program based on its vegetative cycles. In this way, the nutrients that are available in the soil fulfill a specific function in the pasture. Among the essential macronutrients used by savoy grass during its first vegetative stages we have nitrogen, phosphorus, potassium, sulfur, calcium and magnesium. Therefore, these can be in excess and deficient in the soil, in the case of secondary macronutrients they play a fundamental role in the fertilization of savoy grass, participating in the development, yield and protein content.